DEVELOPMENT AND EVALUATION OF NANOSPONGES-BASED BUCCAL TABLETS FOR DELIVERY OF QUERCETIN USING BOX-BEHNKEN DESIGN - GUJJULA, PRAVEEN; PARAMESWARI, ANGALA (International Journal of Applied Pharmaceutics, 2023)
Objective: The goal was to develop a controlled-release formulation of quercetin utilizing the cyclodextrin-based nano-sponges as a nanocarrier. Methods: Based on the preliminary trials a 3-factor, 3-level Box-Behnken design was employed. Five types of nano-sponges from β-cyclodextrin (NS1-NS5) were purposely designed. Quercetin was loaded into nano-sponges by freeze-drying method. The prepared nano-sponges were characterized and formulated into tablets and evaluated for weight variation, hardness, friability, disintegration studies, dissolution and stability studies. Results: The particle sizes of quercetin-loaded nano-sponges are in between 36.45 to 135.27 nm, encapsulation efficiency of 42.37 to 88.44 % and drug release% at 6h of 53.04 to 82.64 %. In vitro release studies showed that more than 90 % of drugs were released from nano-sponge formulations as compared to only around 45% from free drug suspension after 24 h. The FTIR, DSC and XRPD studies confirmed the interaction of Quercetin with nano-sponges. TEM image revealed the spherical structure of drug-loaded nano-sponges. The drug loaded in the nano-sponge structure can be retained and released slowly over time. The nano-sponges were formulated into tablets and evaluated for weight variation, hardness, friability and disintegration studies and obtained satisfactory results. In vitro drug release from a tablet exhibited a maximum release of 99.75 percent with controlled release behaviour over 24 h, and stability studies suggested no major significant changes within 6 mo. Conclusion: Cyclodextrin-based nano-sponges showed superior complexing ability with increased solubility of poorly soluble Quercetin tablets made for controlled drug delivery, which can reduce dosing frequency.